IL-1β Suppresses the Formation of Osteoclasts by Increasing OPG Production via an Autocrine Mechanism Involving Celecoxib-Related Prostaglandins in Chondrocytes - Yusuke Watanabe; Aki Namba; Yukiko Aida; Kazuhiro Honda; Hideki Tanaka; Naoto Suzuki; Hideo Matsumura; Masao Maeno (Hindawi Limited, 2009)
Elevated interleukin (IL)-1 concentrations in synovial fluid have been implicated in joint bone and cartilage destruction. Previously, we showed that IL-1β stimulated the expression of prostaglandin (PG) receptor EP4 via increased PGE2 production. However, the effect of IL-1β on osteoclast formation via chondrocytes is unclear. Therefore, we examined the effect of IL-1β and/or celecoxib on the expression of macrophage colony-stimulating factor (M-CSF), receptor activator of NF-κB ligand (RANKL), and osteoprotegerin (OPG) in human chondrocytes, and the indirect effect of IL-1β on osteoclast-like cell formation using RAW264.7 cells. OPG and RANKL expression increased with IL-1β; whereas M-CSF expression decreased. Celecoxib blocked the stimulatory effect of IL-1β. Conditioned medium from IL-1β-treated chondrocytes decreased TRAP staining in RAW264.7 cells. These results suggest that IL-1β suppresses the formation of osteoclast-like cells via increased OPG production and decreased M-CSF production in chondrocytes, and OPG production may increase through an autocrine mechanism involving celecoxib-related PGs.